1996
DOI: 10.1063/1.116983
|View full text |Cite
|
Sign up to set email alerts
|

Recombination dynamics in InGaN quantum wells

Abstract: Radiative recombination lifetime measurements of InGaN single quantum well

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
59
1

Year Published

1998
1998
2001
2001

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(66 citation statements)
references
References 3 publications
6
59
1
Order By: Relevance
“…Indeed, some InGaN MQW LDs showed EHP lasing in tail states. 25,26,[32][33][34]62 This may cause the increase of threshold current density of InGaN LDs in terms of reduiction in differential gain. Importance of QW exciton localization into the energy tail states was explained in addition to highfield effects in InGaN QWs.…”
Section: Coulomb Screening Effects By Si-doping Of Gan Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, some InGaN MQW LDs showed EHP lasing in tail states. 25,26,[32][33][34]62 This may cause the increase of threshold current density of InGaN LDs in terms of reduiction in differential gain. Importance of QW exciton localization into the energy tail states was explained in addition to highfield effects in InGaN QWs.…”
Section: Coulomb Screening Effects By Si-doping Of Gan Barriersmentioning
confidence: 99%
“…Several groups have assigned the spontaneous emission from InGaN QWs to the recombination of excitons localized at certain potential minima. 1,[25][26][27] On the other hand, several groups have discussed the importance of the quantum confined Stark effect (QCSE) 28 due to the piezoelectric field (F PZ ) in strained wurtzite InGaN QWs. 2,25,[29][30][31] In particular, the blueshift of the electroluminescence (EL) peak in InGaN SQW LEDs 1 with increasing drive current has been explained 1,25 by the combined effects of a reduction of QCSE due to Coulomb screening of F PZ 2,25,29 and band-filling of the energy tail states.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, although a great deal of progress has been made in the development of InGaN-based light emitters, the role played by indium (In) in contributing to the optical efficiency is still quite controversial. A number of groups have proposed that the inhomogeneity of In incorporation results in carrier localization at In-rich regions and that this localization leads to enhanced optical efficiency [73][74][75]. Support of this hypothesis is found in cathodoluminescence experiments that demonstrate a variation of the PL emission energy on the microscale, suggesting that In composition variations on the order of several percent are possible [76].…”
Section: Study Of In-containing Uv Led Alloy Materialsmentioning
confidence: 53%
“…In order to optimize the device design, it is necessary to study and understand the physical properties of nitride MQWs as well as the MQW structural effects on the device performance. Recent work on the III-nitride alloy systems and MQWs has shown that localized excitons dominate the optical transitions in these systems at low temperatures [2][3][4]. And, it has been proposed and shown that piezoelectric fields due to lattice mismatch-induced strain in InGaN/GaN MQWs [5,6] and GaN/AlGaN QWs [6][7][8][9] are the primary reason for the large redshift of the photoluminescence (PL) emission peak.…”
Section: Introductionmentioning
confidence: 99%